PENERAPAN MODEL PEMBELAJARAN DIRECTED READING THINKING ACTIVITY UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN TEKS CERPEN PADA PESERTA DIDIK KELAS IV DI SD INPRES PANGGENTUNGAN SELATAN KABUPATEN GOWA - Dhara Ervitasari, Dhea; Rahmawati Patta; Faidah Yusuf (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to improve the reading comprehension skills of short story texts through the implementation of the Directed Reading Thinking Activity (DRTA) learning model among fourth-grade students at SD Inpres Panggentungan Selatan, Gowa Regency. This research is a classroom action research (PTK) conducted in two cycles, with each cycle consisting of two meetings. The research subject were 35 students. Data collection techniques included observation, learning achievement tests, and documentation. The results showed an improvement in student score in cycles 1 of 68, which significantly increased to 81 in cycle 2. Based on these results, it can be concluded that the implementation of the DRTA learning model can improve the reading comprehension skills of short story texts among fourth-grade students at SD Inpres Panggentungan Selatan.